Vertical Distribution of Forms of Potassium in Rice-based Cropping Systems of Gangetic Alluvial Soil of West Bengal, India - Mondal, Haripada; Kundu, M. C. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during rabi (e.g., November, 2022–April 2023) at the North 24 Parganas district of West Bengal, India. The objective was to assess the K status in rice-based cropping systems of Gangetic alluvial soil of North 24 Parganas Potassium (K) is required for crops, affecting growth, yield, tissue strength, resistance to pests, and activation of enzymes. A total of 225 soil samples were collected from varying depths and rice-based cropping systems and were analysed for different forms of potassium and physico-chemical properties. The results showed extreme variation in the forms of potassium: available K, water-soluble K, exchangeable K, non-exchangeable K, total K, and lattice K with the cropping systems and depths. The Rice-Vegetables system had the highest values of available K, water-soluble K, exchangeable K, and HNO3 soluble K, and the Rice-Rice system had the highest values of non-exchangeable, lattice, and total K. On the other hand, the Rice-Mustard-Jute system had the lowest values in many forms of potassium, except water-soluble K, which was lowest in the Rice-Rice system. Overall, all fractions of K were maximum at 30–45 cm depth and minimum at 15–30 cm depth, increasing with increasing depth of soil. Various forms of potassium significantly and positively correlated with clay content and bulk density, and with each other, resulting in a dynamic equilibrium that was conducive to the supply of K to the crops.